(3GdEOGQI GdESJQGJjLjI ddeDSSI ef NdGd dhMI GdbjGOIs - (3hgjHI(B, (3ebOes ((3GdGScfOQjI (B:s (3OGQ GdJYdje GdLGeYj(B,s, 2020)
(3JfGhd gPG GdcJGH ehVhY GdEOGQI GdGSJQGJjLjI ddeDSSI ef NdGd dhMI GdbjGOI HGYJHGQgG ef Cge GdhXGFa GdEOGQjI, MjK JfGhd YHQ aUhd OQGSJg GdeaGgje GdCSGSjI hGdJhLg GdGSJQGJjLj ddhMI GdbjGOI, HGdGXGaI Gdi eaghe GdEOGQI GdGSJQGJjLjI hHWGbI GdCOGA GdeJhGRf cfehPL eKGdj ddhMI GdbjGOI GdGSJQGJjLjI, cPdc EOGQI eTQhY (B"(3JUeje THcI dhMGJ GdbjGOI aj GdeDSSI(B" (3hGdeQGMd GdYedjI dEfLGRg(B. s
(3HHdjhZQGajG U(B.277 (3bGFeI GdLOGhd U(B.291 (3bGFeI GdCTcGd U(B.293 (3bGFeI GdedGMb U(B.295s
Keywords: (3GdEOGQI GdESJQGJjLjIs; (3GdEOGQI GdbjGOjI s; (3dhMI GdbjGOIs